Relationship between economic indicators and selected social development indicators in the globalization process in Iran (1980-2010) - Moghaddam, Abdolmajid Arfaei (2015)
The majority of globalization theories confirm their impacts on human and social welfare. They suggest both the favorable and unfavorable outcomes. This study presents a dialectical model from economic globalization measurement on social development indicators during 1980 – 2012, and to empirically test the impacts of economic globalization on social consequences. The outcome reveals significant and positive impacts of globalization on economic development indicators in the some developing countries, and so, significant effects of economic indicators generate on three social development indicators of Iran in the past three decades. Whereas, the outcomes of globalization do not generate favorable effects on social development indicators from Iran when economic development indicators level are as control variables. An estimation of overall from two globalization indices is found to generate significantly impacts on the GDP (gross domestic production) of Iran. The human development indices are raised within selected developing countries in the past three decades. The findings of the first objective shows that selected developing countries in this study experienced a more rapid growth in the foreign direct investments (FDI), which surged starting in the early 1980s. Data from these countries indicates that substantial economic growth is related to unprecedented high FDI inflows in the international levels. But, FDI inflow of Iran was not very significant. As, the export and import of goods as merchandise trade in all countries mentioned above has successfully grown with the global economy. As a result, trade performance of Iran has been very weak for Iran, as reflected in its negative balance of trade. Our findings demonstrate the effects of FDI on export and import of goods that predicates a statistical relationship between FDI and foreign trade. The findings of the second objective shows that FDI and merchandise trade play a pivotal role and are the key to economic development in selected countries. Attracting FDI helps to develop higher capacities in foreign trade and increases economic growth rate and gross domestic product (GDP) in these countries. However, the rise of GDP and economic growth rate of Iran is accompanied by the inflection that these results are due to petroleum and other raw materials sales, not from investment in different sectors of society. The analysis of third objective explores the importance and impact of globalization have on the social development of Iran, and reveals a trend of relative improvement and development of a some social indicators like health, education, per capita income and Human Development Index (HDI). The estimates suggest that the Iranian health index improved in two areas: life expectancy and infantile mortality rate below 5 years, during the past three decades. Looking at the education component of Iran, indicating that Iran has successfully grown in the education sector and the literacy rate. The results show that the per capita income of Iran indicating a relatively rise in per capita income of Iranians from 1980 to 2010. In a general overview of HDI outputs, it appears that Iran has benefited with a relatively acceptable rate of improvement in HDI and its indices. So, the results this study, poverty and inequality were shown to have generally stagnated at existing levels without any indication of significant improvement and have not significantly decreased in Iran. Thus, our findings demonstrate that social development in Iran is closely related to economic development, while economic improvement depends on the progress of globalization or integration in international relations. By having created a layout for the development contexts in Iran and pointing out the importance of economic competition in the present and future, society can be lead to social and economic development. Consequently, a decrease in poverty and inequality levels will be manifested. Therefore, the issues relate to development and modernization that go beyond national boundaries and that lead to globalization and integration within a global society, with emphasis on socioeconomic developments, decline of poverty and inequality at all levels in all countries.